Peran Trait Kepribadian terhadap Social Support pada Penderita Kanker Leher Rahim - Clara Assisiansi Dewi Dermawan; Lie Fun Fun (Universitas Kristen Maranatha, 2019)
Based on Data Riset Kesehatan Dasar Indonesia (2013), 65% cases of diseases are caused by non-contagious diseases, one of them is cervical cancer. Individual response to the cancer varies depend on personality and their perception about social support. This study uses McCrae-Costa’s Big Five Personality Theory (2003) and Cohen’s Social Support (2002). Sixty cervical cancer patients, selected by accidental sampling, were given personality and social support questionnaire. Each trait’s score tested its contribution to social support’s score with Multilinear Regression Test by SPPS 20. Agreeableness contributes to perception about appraisal support (F=8.303) and belonging support (F=4.501). Extraversion contributes to perception about appraisal support (F=7.7). Openness to experience contributes to perception about belonging support (F=5.465) and tangible support (F=3.922). Neuroticism and Conscientiousness do not contribute to perception about any social support dimensions. Hopefully this study can be used by the patient’s family, the hospital, and LSM in giving social support and also for the patient to understand about their personality and know what kind of help they do need from people around. Keywords: cervical cancer, big five personality, social support, Multilinear Regression Test